"Study of Managerial Trends for Supply and Consumption of Fule in Great Tehran" - J Nouri; S Azad Zarabadi (Tehran University of Medical Sciences, 2002)
Regarding to the escalating trend of environmental pollutions, especially air pollution in Great City of Tehran, the perspective and study of the conditions for supply and consumption trends of fuels, with specific to fossil fuels, can lead to formation of significant figures and data. On the other hand, recognition, and if possible, reformation of environmental management schemes in the supply and consumption sector for fossil fuels, can turn to be highly, efficient in erasure of the existing imbalance in domestic supply and consumption of fuels. For this purpose, several studies have been taken place to cover the procedures for fuel supply, and to promote management skills in Great City of Tehran. Based upon the findings of this study the utmost consumption rate of fuels, such as oil, gasoline, petrol and natural gas, belongs to the District 4 of Tehran municipality, with nearly %9.34 of Tehran's total fuel consumption figure. By viewing the said percentage, it could be interpreted that the district 4 is the vastest and most populous district in Tehran, and is made of middle and high class social strata. In addition to that, the lowest fuel consumption rate, is, that of Tehran's district 22, with nearly %0.75 of Tehran's total consumption rate, which is due to the fact that, this district has been, recently, annexed to Tehran's Twenty different districts. Meanwhile, district 22 is along side Alborz Mountions strips and Tehran-Karaj motorway: while being less populous, with a social texture made of low income strata and labourers. This study, is based on Coontz and Odanel management theories and managerial five faceted obligations for the overall supply and consumption systems, and for gradual eradication of the current in appropriate fuel supply and consumption trends, which, on one hand, leads to a decline in these produce and resources and, on the other hand, leads to environmental pollutions, specially air pollution, regarding the existing cultral frame work in Tehran and its economic and socio-political status.